Praktik Intervensi Pekerja Sosial dengan Metode Groupwork melalui Terapi Bermain Kelompok terhadap Anak Korban Kekerasan: (Praktik Kerja Lapangan Prodi Kesejahteraan Sosial FISIP USU) - Jodis Simanullang; Fajar Utama Ritonga; Hairani Siregar; Maidinse Hutasoit (Yayasan Literasi Sains Indonesia, 2023)
Recently, cases of violence against children have become more prevalent. In recent years, Indonesia has often been mentioned as facing an emergency of violence against children, be it physical violence, sexual violence, bullying, and so on. The perpetrator even comes not only from the victim's external environment, but also by the victim's closest people and even the victim's own family. Meanwhile, the main concern is the impact experienced by child victims of violence. In the practice of social work, a social worker must strive to achieve evil for the child who is a victim. As a prospective professional social worker, Praktikan practiced social worker intervention with the groupwork method on six child victims of violence. Groupwork methods provide assistance such as self-help groups, achieving common goals in the group and so on. In this case, Praktikan conducts group play therapy for child victims of violence with the aim of reducing bad behavior and increasing the closeness of relationships among fellow clients. Kata Kunci: Metode Groupwork, Terapi Bermain Kelompok, Anak Korban Kekerasan.